Helminthic larval stage induces cellular apoptosis via caspase 9-mediated mitochondrial dysfunction - Sternkopf, Leonardo Elias; Prodjinotho, Ulrich Fabien; Gres, Vitka; Repgen, Nikolaus; Steiger, Katja; Schluckebier, Julia; Sikasunge, Chummy S.; Stelzle, Dominik; Makasi, Charles; Winkler, Andrea Sylvia; Ngowi, Bernard J.; Villalobos, Nelly; et al. (Frontiers in Immunology, 2025)
IntroductionIn human neurocysticercosis (NCC), the cellular and molecular mechanisms of host-parasite interactions triggering brain inflammation and epileptic seizures in Sub-Saharan Africa are poorly understood. Emerging evidence indicates that the viability of the cyst of the pork tapeworm Taenia solium determines brain inflammation and, thus, symptom development and disease severity. We have previously shown that while viable cyst-released molecules promote immune regulation and often asymptomatic disease, the fluid from degenerating cysts causes inflammation in microglia and peripheral immune cells, potentially driving immune-mediated pathology. This study aims to elucidate the apoptotic signaling pathways underlying this process and their relevance for symptomatic disease in NCC patients.Materials and methodsHuman and porcine peripheral immune cells, as well as murine microglia, were exposed to T. solium cyst vesicular fluid (CVF). Apoptosis signaling pathways were analysed using flow cytometric FLICA (fluorochrome-labeled inhibitors of caspases) caspase 8 and 9 assays, while mitochondrial dysfunction was assessed via TMRE and MitoTracker Deep Red and Green fluorescent probes. Apoptosis-inducing CVF molecules were identified by differential mass spectrometry and functionally tested using specific inhibitors. Caspase activity and soluble mediators (FasL, ROS, TNFα) were measured in NCC asymptomatic and symptomatic patients’ sera, and inflammatory T cell infiltrates expressing caspases near viable and degenerating cysts in naturally infected pig brain slices were examined via immunohistology.ResultsWe found that vesicular fluid derived from cysts primarily induced apoptosis and caspase 3 and 9 activity, and only minimal necrosis, in a dose-dependent manner across central and peripheral immune cells. This effect was prominent in CD16+ monocytes, microglia, and in CD3+ T cell-expressing caspase 3 near degenerating brain cysts. Apoptotic signaling was predominantly mediated by a dynamic remodeling of caspase 9 pathway, accompanied by a significant loss of mitochondrial potential and a sharp decrease in Bid and Bcl2 transcription, favoring the intrinsic over the FasL-dependent extrinsic pathway and mechanisms. This process is primarily mediated by small molecules (< 30 kDa), and remained unaffected by heat and proteinase treatment. Notably, symptomatic NCC patients exhibited elevated FasL levels correlating with increased caspase activity, underscoring the potential contribution of apoptosis to disease pathogenesis.ConclusionsThis study identifies caspase 9-mediated apoptosis as a mechanism of helminth-induced brain inflammation and implicates FasL in symptomatic disease progression. These insights enhance our understanding of NCC immunopathogenesis and may inform future therapeutic strategies targeting apoptotic pathways.